Validation of two handheld devices against a non-portable three-dimensional surface scanner and assessment of potential use for intraoperative facial imaging. Issue 1 (January 2020) - Koban, Konstantin Christoph; Perko, Philipp; Etzel, Lucas; Li, Zhouxiao; Schenck, Thilo Ludwig; Giunta, Riccardo Enzo
Summary: Background: The aim of this study was to compare accuracy and timing of two handheld, mobile three-dimensional surface imaging (3DSI) devices against an established non-portable medical imaging system, and to evaluate future intraoperative use for facial surgery. Methods: Surface-to-Surface root mean square analysis was used to evaluate both a consumer device (Sense 3D) and a professional surface scanner (Artec Eva) against a reference imaging system (Vectra XT). Two assessors repeatedly 3D-imaged the facial region of an imaging phantom and 30 volunteers in two separate sessions. Using both mobile devices, intraoperative 3DSI of 10 rhinoplasty patients was compared with preoperative reference imaging. Intraclass Correlation Coefficient was calculated for repeated measurements. Results: Artec Eva yielded mean deviations below 0.5 mm for the whole face and all subunits excluding the eye region. Sense 3D showed similar deviations for the whole face, but otherwise only in the central and lateral forehead unit and the medial cheek. Variability was low for both the non-portable Vectra XT and Artec Eva, whereas full-face assessment using Sense 3D resulted in high variability. When compared to the preoperative reference images, intraoperative rhinoplasty 3DSI revealed low deviations for Artec Eva and high deviations for Sense 3D. Conclusions: The 3D surfaces captured by Artec Eva showed a similarly desirable accuracy for facial imaging as Vectra XT reference images. This handheld device presents a suitable option for the objective documentation during rhinoplasty surgery. Sense 3D was unable to accurately capture complex facial surfaces and is therefore limited in its usefulness for intraoperative 3DSI.